2015
DOI: 10.1186/s12891-015-0806-9
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the German version of the STarT-Back Tool (STarT-G): a cohort study with patients from primary care practices

Abstract: BackgroundCurrent research emphasizes the high prevalence and costs of low back pain (LBP). The STarT Back Tool was designed to support primary care decision making for treatment by helping to determine the treatment prognosis of patients with non-specific low back pain. The German version is the STarT-G. The cross-cultural translation of the tool followed a structured and widely accepted process but to date it was only partially validated with a small sample.The aim of the study was to test the psychometric p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
57
3
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 43 publications
6
57
3
4
Order By: Relevance
“…Similar results with respect to fear of movement have been observed in later cross-cultural validation studies of SBT [29][30][31][32] . SBT total and/or psychosocial subscale scores have shown to be associated with LBP-related disability, bothersomeness, catastrophizing, and depression/ depressive symptoms 5,13,[29][30][31][32][33][34][35] . Emotional and behavioural problems were strongly associated with multisite musculoskeletal pains in an earlier population-based study 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Similar results with respect to fear of movement have been observed in later cross-cultural validation studies of SBT [29][30][31][32] . SBT total and/or psychosocial subscale scores have shown to be associated with LBP-related disability, bothersomeness, catastrophizing, and depression/ depressive symptoms 5,13,[29][30][31][32][33][34][35] . Emotional and behavioural problems were strongly associated with multisite musculoskeletal pains in an earlier population-based study 36 .…”
Section: Discussionmentioning
confidence: 99%
“…The difference in pain and activity limitations between the low and the medium risk groups supports the suggestions that the groups should be offered different treatment. No participants were allocated into the high risk group in this study, in contrast to what has been reported previously [19, 28, 29]. The reason for this may be that our participants were recruited from patients treated by physiotherapists (PT) in primary health care, while others have recruited patients from general practices (GP) [29] and from both GP and PT [30].…”
Section: Discussionmentioning
confidence: 99%
“…has generated great interest in developed countries, providing new hope that meaningful improvements in primary care for LBP are within reach. [14][15][16][17][18][19] Prior to widespread implementation, it would be valuable to know if the STarT Back strategy can be successfully translated to other settings. To determine if the STarT Back risk stratification strategy would succeed in the USA, we conducted the Matching Appropriate Treatments to Consumer Healthcare needs (MATCH) cluster randomized trial.…”
Section: Introductionmentioning
confidence: 99%